Government experimentation in business, - Persons, Warren M. (Warren Milton), 1878-1937 (J. Wiley & Sons; Chapman & Hall, 1934)
"An outgrowth and expansion of an historical survey made December 22, 1933 for the information of the Edison electric institute."--Foreword. "References": pages 239-258. "Authorities": pages 259-261.